PENGARUH PENGANGGURAN DAN KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBIPERIODE 2019-2023 - Revina Juwita Sari; M. Nazori (ICONS: Islamic Economics Journal, 2025)
Quality economic growth can be achieved through policies that expand employment opportunities (reducing the unemployment rate) and maximize productive investment in various economic sectors. This research aims to conduct an analysis of the factors that influence economic growth in Jambi Province in the 2019-2023 period from an Islamic perspective. This research is an associative type of quantitative research with the data used being secondary data. The population in this research is 11 regencies/cities in Jambi Province, and the sample used in this research is data on unemployment, poverty and economic growth in Jambi Province. The research data was processed using panel data regression analysis techniques. The results of the analysis show that simultaneously unemployment and poverty have a significant effect on economic growth in Jambi Province for the 2019-2023 period. Partially, unemployment has a significant negative effect on economic growth in Jambi Province for the 2019-2023 period and poverty has a significant negative effect on economic growth in Jambi Province for the 2019-2023 period.